ÜNİVERSİTE ÖĞRENCİLERİNDE OBEZİTE SIKLIĞI, FİZİKSEL AKTİVİTE DÜZEYİ VE SAĞLIKLI YAŞAM BİÇİMİ DAVRANIŞLARININ İNCELENMESİ - MURATHAN, FATİH (Fırat Üniveristesi, 2013)
Obezite hem gelişmiş hem de gelişmekte olan ülkelerde görülme sıklığı artan, çocukları olduğu kadar, giderek erişkinleri de etkileyen kronik bir hastalıktır. Günümüzde obezitenin görülme sıklığı her yaş grubunda artmaktadır. Bunun nedeni modern yaşamın getirdiği beslenme alışkanlıklarının bozukluğu ve bireylerin fiziksel aktiviteden uzaklaşarak hareketsiz bir yaşam sürmeleridir. Üniversite öğrencilerinde obezite sıklığı belirlemek, fiziksel aktivite düzeyi ile sağlıklı yaşam biçimi davranışlarını incelemek amacıyla yapılmış olan bu araştırma Adıyaman Üniversitesi?nde 2012-2013 eğitim öğretim yılında öğrenim gören öğrencilere uygulanmıştır. Elde edilen veriler istatistik paket programında analiz edilmiştir. Merkez kampüste öğrenim gören 9264 öğrencinin 1260?ına ulaşılmıştır. Araştırmada deneklere antropometrik vücut ölçümü yapılmış olup fiziksel aktivite düzeyi ve sağlıklı yaşam biçimi davranışları ölçeği uygulanmıştır. Araştırma sonucu veriler incelendiğinde araştırmaya katılan üniversite öğrencilerinin % 47,94?ünü (604 öğrenci) erkek, % 52,06?sını (656 öğrenci) kadın öğrencilerin oluşturduğu tespit edilmiştir. Bunun sonucunda araştırmaya katılan üniversite öğrencilerinin 815 (%64,69)?unun normal kilolu, 322 (%25,55)?inin fazla tartılı, 123 (%9,76)?sının ise obez olduğu tespit edilmiştir.

Obesity is a chronic disease which affect the adults more day by day as well as children and prevalance of which has been increasing in both developed and developing countries. Recently,prevalance of the obesity has increased at any age groups. the reason for this is the breaking of the food habits introduced by the modern life and individual's maintaining a sedentary life style avoiding from the physical activities. This research which has been carried out to determine the frequency of obesity among the university students and analyze healthy life style behaviors with the level of physical activity was Performed upon the students studying at Adıyaman University in 2012-2013 academic year. 1260 of the 9264 students studying in the central campus were reached. Anthropometric body measurements were performed upon the experimental subjects in the research, and level of physical activity and healthy life style behaviors scale was performed. When the data were analyzed as result of the research, 47,94% (604 students) of the university students participated in the research were determined as male and 52,06% (656 students) were determined as female. When age variable of the students was anlyzed, 31,12% of the students were determined as being 18 years old and below, 52,69% as being between 18-23 years old and 16,19% as being 24 years old and over. As result of this, 815 (64,69%) of the university students participated in the research were determined as having normal weight, 322 (25,55%) were deetrmined as being overweight and 123 (9,76%) were determined as being obese.
Obesity frequency of the university students and analyzing the level of physical activity and healthy life style behaviors
Keywords: Sağlık Eğitimi; Spor